Local bifurcations and global dynamics in a solow-type endogenous business cycles model - Gomes, O. (2017)
Neoclassical growth models are essentially characterized by the formation of a steady state where the main economic aggregates (capital, output, consumption and investment) do not grow, unless some external event takes place (e.g.,technological progress or population growth). Hence, the long term result corresponds to a fixed point and any kind of endogenous fluctuations is ruled out. This paper introduces an inefficiency mechanism through which non perfect firms’ expectations about future demand conduct to underinvestment, which originates periodic and a-periodic long run cycles; this mechanism is applied over the simplest neoclassical growth model, the Solow equation regarding capital accumulation. Results, containing a large variety of dynamic features, are discussed through the analysis of local bifurcations and through numerical examples that give insights about global dynamics.